Determination of Levels of Phytochemical Compounds (Saponins, Alkaloids, Tannins) In Ripe Fiber Extract of Palmyra Fruit (Borassus flabellifer Linn) - Tince Bety Amarduan; Yulia Sari; Brian Wasita (Future Science, 2024)
Palmyra fruit (Borassus flabellifer L.) is one of the palm tree family that can be utilized as a source of of food. It also possess numerous benefits in medicinal applications, including secondary metabolites in the form of alkaloids, flavonoids, saponins, tannins, and terpenoids. All of which exhibit antioxidant, anti-inflammatory, and antimicrobial. Therefore, it is imperative to conduct quantitative phytochemical analysis to garner the composition of each compound in Palmyra fruit. This study aims to determine the level of saponins, alkaloids, and tannins in Palmyra fruit fiber extract originating from Werain village, Selaru, West Southeast Maluku. The extraction process was done using the maceration method with 96% ethanol solvent. Method: This study is geared toward quantitative laboratory-scale experiments to determine the sample level. Saponin and alkoloids were analyzed using gravimetry methods while tannins were analyzed using UV-Vis spectrophotometric. Results: it is revealed that saponins level is 1,02%; Alkaloids level is 1,5464; and tannins level is 1,0220%. Conclusion: The presence of saponins is 1,02%; Alkaloids is 1,5464; and tannins is 1,0220%.